IMPLEMENTASI BISNIS MODEL CANVAS PADA INDUSTRI RUMAH TANGGA MOSES PROFESIONAL LAUNDRY (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2022)
Community service in the Community Partnership Program (PKM) is carried out in the MosesProfessional Laundry business. The Moses Professional Laundry business is a promising business, this issupported by a strategic location close to apartments, hotels, homestays, and even offices. The businessmanagement of Moses Professional Laundry (MPL) has not been carried out professionally, so manycustomer complaints regarding MPL's performance include: laundry that is not completed on time,ironing results are less slippery, many customers' clothes are missing, and the delay in resolvingcomplaints. With conditions like this, many customers switch to other laundry. MPL's main problems arein the areas of management, production and marketing. The purpose of this community service is toprovide training and assistance in implementing the 9 elements of the Business Model Canvas (BMC).The method of service implementation is training and mentoring: the use of an LPG electric converterdryer machine, dryer room infrared, fast and smooth steam ironing techniques, partnership managementtechniques, techniques for determining market segmentation, cataloging and brochures, cost efficiency,control management, service techniques and maximum utilization of resources. The results of this serviceinclude: increased production volume, profits, employee skills, customer satisfaction, and quality control.Keywords: BMC, Laundry, Management, Marketing, Service